A Comment on: “State Capacity, Reciprocity, and the Social Contract”by Timothy Besley - Papaioannou, Elias (Econometrica, 2020)
In this note, I discuss avenues for future research stemming from Besley's [this issue] theoretical approach on the interconnections between civicness, institutions, and state‐fiscal capacity. First, I lay down some ideas on how one could extend the framework to model fragility traps that characterize many low‐income countries and study issues related to nation‐building, conflict, and heterogeneity across space and ethnic lines in the provision of public goods. Second, I discuss the relevance of the approach for the analysis of authoritarian populism that is spreading in developed countries and emerging markets.